Terapia adjuvantă cu imunomodulatori în oncologie - Ioana Chiţescu; Diana Mihaela Alexandru; Răzvan Ionuț Dobre; Maria Crivineanu (Medicamentul Veterinar, 2023)
In the field of oncology immunotherapy, remarkable discoveries have been made în recent years. The aim of this paper is to cover recent findings în oncology immunotherapy, including the use of inhibitory T cells, modified T cells, anti-cancer vaccines and anti-B and T antibodies. In veterinary oncology, immunotherapy is increasingly used due to impressive results. Modified T-cell therapy has demonstrated remarkable tumour control and regression în human subjects, and anticancer vaccines have recently demonstrated long disease-free periods and increased survival time în dogs with lymphoma. Thus, due to the clinical effects obtained, immunomodulators are successfully used în veterinary oncology therapy.